The Transnational Families - Aguilar Díaz, Richard (2015)
Considering the continuing evolution of the traditional family model interstate factors (personal, legal and economic) and international (migration), giving rise to new family models, it is necessary to know whether or not these models enjoy legal recognition and protection thus family arranged by state constitution and laws.